Implementasi Kebijakan Pengelolaan Parkir di Tepi Jalan Umum Kota Semarang Tahun 2022 - Gunawan, Gunawan; Nuh, Muhammad (JURNAL LANSKAP POLITIK, 2023)
This paper aims to determine the implementation of parking management policies on public roads in Semarang in 2022. By using qualitative research methods, the results of this study show that the implementation of parking management policies on public roads in Semarang in 2022 is still not optimal, especially in terms of limitations. information regarding the existence of a mayoral regulation that regulates parking on the side of public roads and the disposition/attitude of policy implementers, in this case parking attendants, who are very lacking in terms of obedience and adherence to following applicable regulations.